2020
DOI: 10.1038/s41598-020-62274-7
|View full text |Cite
|
Sign up to set email alerts
|

Immune dysregulation among students exposed to exam stress and its mitigation by mindfulness training: findings from an exploratory randomised trial

Abstract: Psychological distress persisting for weeks or more promotes pro-inflammatory immune dysregulation, a risk factor for a range of chronic diseases. We have recently shown that mindfulness training reduces distress among university students. Here we present an exploratory trial to study immune dysregulation in a cohort of students who were exposed to progressively greater stress as the exam period approached, and to explore whether mindfulness training mitigated this dysregulation. Healthy University of Cambridg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 71 publications
(95 reference statements)
2
12
0
3
Order By: Relevance
“…En estos, se observó una relación entre el dominio del mindfulness y una frecuencia cardíaca basal elevada, lo cual puede ser un factor de riesgo coronario (Brzozowski, et al, 2018). Al mismo tiempo, mientras que no se pudo asociar el mindfulness a parámetros inmunológicos, el aumento de la angustia sí que apareció asociado a una desregulación inmunológica con procesos proinflamatorios (Turner, et al, 2020). Respecto al uso específico de los programas, se demuestra que las intervenciones basadas en mindfulness (MBI) optimizan dominios de ansiedad, depresión y estrés (Cavanagah, et al, 2018;Wimmer, et al, 2020); la autoayuda basada en mindfulness (MBSH) y el programa de entrenamiento en mindfulness (MTP) reducen significativamente el estrés (Gu, et al, 2018;Moore, et al, 2020); la terapia cognitiva basada en atención plena (MBCT) mejora las creencias sobre emociones, autocompasión, perfeccionismo y descentramiento (James & Rimes, 2018); y por último, la reducción del estrés a través del mindfulness (MBSR) conlleva un progreso en términos de disminución de reactividad, aumento de curiosidad, tolerancia afectiva, paciencia, autoaceptación, y cualidades relacionales (Solhaug, et al, 2016).…”
Section: Propósito Resultados Y Programa Mindfulness Utilizadounclassified
See 2 more Smart Citations
“…En estos, se observó una relación entre el dominio del mindfulness y una frecuencia cardíaca basal elevada, lo cual puede ser un factor de riesgo coronario (Brzozowski, et al, 2018). Al mismo tiempo, mientras que no se pudo asociar el mindfulness a parámetros inmunológicos, el aumento de la angustia sí que apareció asociado a una desregulación inmunológica con procesos proinflamatorios (Turner, et al, 2020). Respecto al uso específico de los programas, se demuestra que las intervenciones basadas en mindfulness (MBI) optimizan dominios de ansiedad, depresión y estrés (Cavanagah, et al, 2018;Wimmer, et al, 2020); la autoayuda basada en mindfulness (MBSH) y el programa de entrenamiento en mindfulness (MTP) reducen significativamente el estrés (Gu, et al, 2018;Moore, et al, 2020); la terapia cognitiva basada en atención plena (MBCT) mejora las creencias sobre emociones, autocompasión, perfeccionismo y descentramiento (James & Rimes, 2018); y por último, la reducción del estrés a través del mindfulness (MBSR) conlleva un progreso en términos de disminución de reactividad, aumento de curiosidad, tolerancia afectiva, paciencia, autoaceptación, y cualidades relacionales (Solhaug, et al, 2016).…”
Section: Propósito Resultados Y Programa Mindfulness Utilizadounclassified
“…En este sentido, se han encontrado artículos que analizan los efectos a nivel psicológico y emocional (estrés, ansiedad, depresión, resolución de conflictos, resiliencia, bienestar, motivación), a nivel de rendimiento académico y dos estudios a nivel fisiológico (inmunología y parámetros cardiovasculares). A nivel general se han encontrado resultados positivos en todos los estudios a excepción de dos que no pudieron concluir mejorías significativas asociadas al entrenamiento en atención plena (Turner, et al, 2020;Wimmer, Bellingrath & Von Stockhausen;.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Persisting psychological stress has been linked with promoting proinflammatory immune dysregulation. 35 In a meta-analysis conducted by Segerstrom and Miller 36 exploring the association between psychological stress and immune function, brief stressors seemed to suppress cell-mediated immune response while preserving humoral immune response. Chronic stress was associated with suppression of both above immunities.…”
Section: Stressmentioning
confidence: 99%
“…In 2015, Nature published an article arguing that the underlying neural mechanisms and the molecular bases of the changes in the brain that accompany mindfulness training remain unclear (Tang et al, 2015: 213). Other researchers reported that they found no evidence that mindfulness training has any effect on participants' immune systems (Turner et al, 2020). More bad news has been emerging to cast a shadow on the dream cure as large-scale experiments and meta-analyses have found that mindfulness could in fact negatively affect task motivation due to the inherent tension between encouraging the workers' acceptance of their present experience and the motivation necessary for taking initiatives and achieving something new (Hafenbrack and Vohs, 2018).…”
Section: The Neoliberal Shift and Mindfulnessmentioning
confidence: 99%